Analysis of Thresher Shark (Alopias pelagicus) Conservation Policy and the Role of Local Communities in Conservation in Indonesian Waters - Soares, Yohanes; Bunyani, Nur Aini; Finmeta, Abdonia W. (Jurnal Biologi Tropis, 2025)
The population of the pelagic thresher shark (Alopias pelagicus) in Indonesian waters continues to decline due to intense fishing pressure and weak implementation of conservation policies. This study aims to analyze the effectiveness of Indonesia’s thresher shark conservation policies and to assess the role of local communities in supporting conservation efforts. A qualitative descriptive approach was applied through literature review, policy document analysis, and interviews with relevant stakeholders, including fishers, local authorities, and conservation organizations. Data were analyzed using content analysis to identify gaps between policy formulation and field implementation. The findings show that although national regulations protect A. pelagicus, their enforcement remains limited due to inadequate monitoring, lack of public awareness, and insufficient livelihood alternatives for fishers. Local communities possess significant potential to contribute to conservation through community-based monitoring and marine ecotourism initiatives. The study concludes that successful conservation of the thresher shark requires stronger synergy between national policies and local initiatives. Key recommendations include strengthening community capacity, enhancing law enforcement, and developing sustainable economic incentives that support conservation.